Global and national public awareness and interest in glomerular diseases from 2004 to 2024 - Balakrishnan, Suryanarayanan; Thongprayoon, Charat; Craici, Iasmina M.; Cheungpasitporn, Wisit; Miao, Jing (Frontiers in Nephrology, 2025)
BackgroundGlomerular diseases significantly impact global health. This study investigated public interest in five common glomerular diseases.MethodsGoogle Trends™ were used to analyze search activity from January 2004 to December 2024 for IgA nephropathy (IgAN), membranous glomerulonephritis (MN), focal segmental glomerulosclerosis (FSGS), lupus nephritis (LN), and diabetic nephropathy (DN). Data were retrieved both globally and in English-speaking countries, including the United States. Monthly and yearly relative search activity were assessed and compared.ResultsGlobally, IgAN had the highest average relative search activity, followed by DN, FSGS, LN, and MN. Both IgAN and FSGS exhibited declining trends, while LN showed an upward pattern. MN and DN experienced a modest decline before 2016, preceded by a slight increase. Among English-speaking countries, search interest was predominantly concentrated in five countries, primarily including the United States, United Kingdom, Canada, and Australia, with the United States consistently ranking as the leading country. For IgAN, LN, and MN, the trends observed in the United States appeared to align with global data. In contrast, search interest for FSGS exceeded global levels, while interest in DN was slightly lower than global activity. In the United States, IgAN, FSGS, and LN were most prominent in North Dakota, Massachusetts, and Delaware, respectively, while DN and MN saw peak activity in West Virginia.ConclusionPublic engagement with glomerular diseases has not uniformly grown, at least in English-speaking countries, emphasizing the need for enhanced awareness efforts. Future analysis should prioritize search terms in the predominant language of each country.